Surface Roughness Analysis of Subsea Cables/Umbilicals - Ahmed Reda; Han Eng Low; Mohamed A. Shahin (Journal of Marine Science and Engineering)
Surface roughness is an important factor influencing subsea cable/umbilical–soil interaction. The cable/umbilical goes through several steps before being laid on the seabed, including production, spooling, unspooling, and installation on the seabed. Yet, there is no standard method for assessing the outer sheath roughness, whether extruded or roving, of subsea cables/umbilicals, and outer sheath roughness has not been measured in many cable/umbilical–soil test datasets. The lack of a universally agreed method for assessing and preparing surface roughness stems from the diverse applications of cables/umbilicals, each of which is subject to varying environmental conditions and operational requirements. Such diversity complicates the establishment of a single standard. The objective of this paper is to present the measurements used to determine the surface roughness of the extruded outer and roving outer sheath of subsea cables/umbilicals. The surface roughness of the outer sheath of subsea cables/umbilicals is required for the soil interface direct shear tests, and the corresponding results are essential for determining the friction factors of the cable/umbilical–soil interaction on the seabed.